(untitled) (Raparin Journal of Humanities (RJH), 2026)
Public employment is one of the most vital areas within administrative law. It plays a central role in the structure of public administration, particularly when it comes to defining who holds positions in government service—commonly known as civil servants. Civil servants form the backbone of the administrative system. The efficiency and success—or failure—of government operations largely depend on how well these employees perform their duties and how effectively they apply the law in practice. Their performance directly impacts the protection of public rights, especially financial rights guaranteed under existing laws. When someone takes on a public role, the law grants them a set of rights and benefits. One of the most significant of these is the right to financial compensation. Once a civil servant is legally appointed, they become entitled to all the financial and professional rights defined by the legislature for that role. This makes the system governing civil servants’ financial rights a cornerstone of public administration. It’s built on a legally defined relationship between the employee and the state. In Iraq and the Kurdistan Region, these financial rights are determined strictly by law, leaving the government no room to alter them arbitrarily. This legal certainty ensures that civil servants’ financial entitlements are protected and upheld.